2016
DOI: 10.1177/0038040716635718
|View full text |Cite
|
Sign up to set email alerts
|

School Racial Composition and Parental Choice

Abstract: Racial segregation remains a persistent problem in U.S. schools. In this article, we examine how social psychological factors—in particular, individuals’ perceptions of schools with varying demographic characteristics—may contribute to the ongoing structural problem of school segregation. We investigate the effects of school racial composition and several nonracial school characteristics on white parents’ school enrollment decisions for their children as well as how racial stereotypes shape the school choice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(78 citation statements)
references
References 67 publications
2
75
0
1
Order By: Relevance
“…A study of upstate New York metropolitan areas-demographically similar in many respects to Pennsylvania-found that White parents' school choices were strongly influenced by wanting their children to attend a school with fewer non-Whites (Lankford & Wyckoff, 2005). A more recent study echoes these issues, showing that given hypothetical school choices, White parents are less likely to select a school if it has a high percentage of Black students, even if the school is rated as high performing (Billingham & Hunt, 2016; see also Holme, 2002). Finally, a national analysis of students' choices in 2003-04 found that school racial composition was not a significant predictor for students moving to charter schools.…”
Section: Understanding School Choicesmentioning
confidence: 99%
“…A study of upstate New York metropolitan areas-demographically similar in many respects to Pennsylvania-found that White parents' school choices were strongly influenced by wanting their children to attend a school with fewer non-Whites (Lankford & Wyckoff, 2005). A more recent study echoes these issues, showing that given hypothetical school choices, White parents are less likely to select a school if it has a high percentage of Black students, even if the school is rated as high performing (Billingham & Hunt, 2016; see also Holme, 2002). Finally, a national analysis of students' choices in 2003-04 found that school racial composition was not a significant predictor for students moving to charter schools.…”
Section: Understanding School Choicesmentioning
confidence: 99%
“…This pathology is attached to both the students who attend them, as children deemed difficult to educate because they are underperforming, unruly, and culturally deficient, and the institutions themselves, as organizations assumed to be underresourced, overextended, and incapable of providing a quality education (Aggarwal, 2016; Lipman, 2009). Assumptions about school demographics therefore influence not only stakeholders’ interactions with the school community but also their perceptions of school quality (Billingham & Hunt, 2016; Cucchiara, 2013; Saporito & Lareau, 1999). As they navigate policies and frameworks that position families as consumers in an educational marketplace (Cucchiara, 2013; Labaree, 1997), advantaged families frequently hesitate to view schools serving predominantly low-income students and students of color as places in which their children can or should belong.…”
Section: Analytic Framework and Related Literaturementioning
confidence: 99%
“…Additional reasons that charter schools, as well as other schools of choice, maintain homogenous student populations rest on the understanding that families of different social class use different criteria to select schools and homes (Lareau & Goyette, 2014). Parents within school choice environments make choices that reflect an array of logics that range from different perceptions of school quality and performance, segregated social networks, alternate educational goals, and explicit or implicit racism (Bell, 2009;Berends & Zottola, 2009;Billingham & Hunt, 2016;Holme, 2002;Marsh, Carr-Chellman, & Sockman, 2009). Charter schools recruit high proportions of minority students for specialized programs (Rapp & Ecks, 2007).…”
Section: Charter and Traditional Public Schools And Diversitymentioning
confidence: 99%